A review on spectrum allocation in cognitive radio network. (29th May 2019) - Singh, Wangjam Niranjan; Marchang, Ningrinla
Cognitive radio is a recent technology that enhances the usage of spectrum resources. Efficient assignment of unused spectrum to unlicensed users is an important problem. Spectrum allocation is an important mechanism that limits and avoids the interference between cognitive radio devices and licensed primary users, thus enabling a better efficient usage of the wireless radio spectrum. In this paper, we present a study of different approaches and techniques w.r.t. spectrum allocation in cognitive radio network. We not only compare them in terms of the assignment scheme, execution model, etc. but also highlight their contributions and shortcomings. Additionally, we also highlight the security attacks on spectrum allocation. The challenges that a CR spectrum allocation technique should take into consideration are also discussed in the end with the hope of aiding future research.